Pengaruh Kompetensi, Teknologi Informasi, Sistem Akuntansi, Internal Control terhadap Akuntabilitas Pemerintah Desa dalam Mengelola Keuangan Desa (Studi Empiris di Kecamatan Pangkalan Kuras Kabupaten Pelalawan Tahun 2018) - Widia Yulianti; Kamaliah Kamaliah; Muhammad Rasuli (Jurnal Ekonomi, 2019)
The purpose of this study was to look at the effect of competency, information technology, accounting systems, internal control, on the accountability of village governments in managing village finances in Pangkalan Kuras Subdistrict, Pelalawan Regency in 2018. The population in this study was village government in Pangkalan Kuras District, Pelalawan Regency which consists of 16 villages. Census technique was used in sampling where all populations were sampled. This is done because the population to be studied is a small number. Each village was taken by 4 respondents related to village financial management, namely the village head, village secretary, treasurer, and finance chief. The number of respondents in this study were 64 respondents. The data analysis method used is multiple linear regression using the SPSS program. Competence of officials in village financial managers is classified as good, information technology in village financial management has been well utilized by the authorities, the village financial accounting system has been in accordance with it, internal control in managing village funds has gone well and village financial management is accountable. Then from the test results obtained the results that the competence of the village financial management apparatus, information technology utilization, village financial accounting systems and internal control have a significant effect on the accountability of village financial management in the village government in Pangkalan Kuras District, Pelalawan Regency.